Characteristics of HPV-unvaccinated undergraduate health students in Switzerland, a cross sectional study - Mona Amadane; Charlotte de Pree; Manuela Viviano; Pierre Vassilakos; Emilien Jeannot; Patrick Petignat (BMC, 2019)
Abstract Background Human Papillomavirus (HPV) vaccination, intended for young women aged 11-14 years old, has been introduced in Switzerland in 2007. Ten years after its introduction, only a few studies have explored the reasons associated with uptake and non-uptake of the vaccination. Our objective was to identify the sociodemographic characteristics of a population of vaccinated and unvaccinated undergraduate healthcare female students, to define the reasons of non-uptake of vaccination, and compare our findings with those found in other Swiss cantons. Methods Between January and November 2017, women studying in Health Sciences School and Medical School in Geneva, aged 18-31 years old, were recruited in a large trial assessing HPV prevalence. As part of a smaller, observational study nested in this larger trial, women were invited to complete a questionnaire. Self-reported HPV vaccination uptake or non-uptake, as well as knowledge and attitude about HPV vaccination were assessed. T-Test and Chi square test were used to compare characteristics of vaccinated and unvaccinated women. Results Overall, 409 women were recruited in the study. The majority of them (69.1%) reported having been vaccinated for HPV, while 30.9% of them had never received any dose of the HPV vaccine. The only factor associated with a higher vaccination rate was the participants' origin, as women from Geneva were more represented in the vaccinated group than women from other Swiss regions or countries. Unvaccinated women were more likely to consider HPV vaccination as less important than the vaccinated ones (50.4% vs 3.5% p < 0.001). Conclusion Although no typical profile can be established in this studied population of unvaccinated women, a lack of information was a major reason of non-uptake of vaccination among the study participants. An effort by health authorities and carefully designed messages are essential to increase the population's awareness over cervical cancer and its prevention. Trial registration The trial was registered under cliniclatrials.gov with the identifier: NCT03474211.